Poverty Reduction Support Credits in Uganda : Results of a Stocktaking Study - Miovic, Peter (World Bank, Washington, DC, 2013)
Uganda pioneered the use of budget support operations known as Poverty Reduction Support Credits (PRSCs) in the World Bank. PRSCs were designed to channel programmatic lending to support policy and institutional reforms in support of a country's Poverty Reduction Strategy, usually presented in the form of a Poverty Reduction Strategy Paper (PRSP). In the case of Uganda the PRSCs were designed as a series of annual credits supporting a three year rolling program of reforms, based on Uganda's version of a PRSC, which is known as the Poverty Eradication Action Plan (PEAP) . The World Bank credits are in the form of untied budget support, financing all government activities, in the same way as domestic tax revenues. The PRSCs have been significantly co-financed by other donors in the form of grants which, like the World Bank credits take the form of untied budget support. The focus of this report is to study what has worked, what has not worked, and what could be improved in the Uganda PRSC process in the future.